The role of competitors in the enforcement of state aid law - Pastor Merchante, Fernando (European University Institute, 2014)
State aid law is made up of rules and procedures whose main characters are the Member States – as the addressees of the norms – and the Commission – as their enforcer. The prominent position of these two actors often overshadows the impact that the administration of the rules on State aid has on private undertakings, be it the beneficiaries of State aids or their competitors. This thesis is concerned with the latter. The aim of the thesis is to assess the extent to which competitors may rely on the rules on State aid to protect themselves against the potentially harmful effects of subsidies and other forms of state, financial assistance to firms. This endeavour raises two challenges. The first challenge is to identify the channels through which competitors may voice their interest in the context of a system of governance to which they are in principle alien. This is the issue of access. The second challenge is assess the likelihood that the Commission shall heed to the concerns voiced by competitors. In other words, the challenge is to gauge the power of influence that competitors may exert through each of these channels. This is the issue of leverage. In order to carry out this inquiry, the thesis scrutinizes the means of redress available to competitors before national courts (“private enforcement”), as well as the opportunities that they have to make their voice heard in the course of the Commission’s procedures (“public enforcement”) – namely, the possibility to lodge complaints, the possibility to participate in the consultation phase of Article 108(2) TFEU and the possibility to seek the judicial review of State aid decisions.
Accepted: 2015-02-09T14:56:15Z
Keywords: Antitrust law; European Union countries; Government aid; Restraint of trade; Subsidies; Unfair Competition